INTEGRATING LANGUAGE SKILLS FOR EFFECTIVE LANGUAGE TEACHING - Buranova, Mekkamtosh (University Research Base, 2025)
This article explores the importance of integrating various language skills—listening, speaking, reading, and writing—in language teaching. It highlights the benefits of skill integration, such as enhanced communicative proficiency, increased student engagement, and the development of critical thinking. The paper discusses several strategies for integrating language skills, including project-based learning (PBL), task-based language teaching (TBLT), and content and language integrated learning (CLIL). Furthermore, it provides practical methods for implementing integrated tasks and offers solutions to potential challenges such as resource limitations, time constraints, and student resistance. By adopting a holistic approach to language instruction, educators can foster a more realistic and effective learning environment, better preparing students for real-world communication.